Do Intrinsic Rewards Matter on Motivation? Evidence from Primary School Teachers of Bangladesh - Anjum, Nishath; Islam, Md. Afsarul; Choudhury, Mahmudul Islam; Saha, Jace (SEISENSE Journal of Management, 2021)
Purpose- This study investigates the impact of intrinsic rewards (Recognition, Training and Development, Work Environment, Participation in Decision Making, and Workplace Flexibility) on primary school teachers’ motivation at the workplace. Design/Methodology- A survey was conducted using a 5 Likert scale questionnaire among the teachers of different primary schools across Bangladesh. A total of 200 data was gathered through random sampling. SPSS 22.0 is used for analyzing the data. The study employed multiple regression and ANOVA, correlation, reliability test, and descriptive statistics to draw the findings. Findings- The study revealed that intrinsic rewards have a significant effect on teachers’ motivation. All the studied variables (Recognition, Training and Development, Work Environment, Participation in Decision Making, and Workplace Flexibility) have found a statistically significant relationship with Motivation. Moreover, recognition and work environment showed the most robust relationships with teachers’ motivation. Practical Implications- Organizations can use this study's results to comprehend the effect of intrinsic or non-financial rewards on employee motivation. Thus, the research findings could help similar institutions design an appropriate reward package with adequate intrinsic rewards to motivate their employees and ensure better performance at work.